Ethnobotanical uses of Plantaginaceae taxa in Türkiye - Doğan, Şule; Tınas, Recep Faruk; Yeşil, Yeter (Ethnobotany Research and Applications, 2026)
Background: The Plantaginaceae family comprises several genera with long-standing ethnobotanical relevance in Türkiye, particularly Plantago, Veronica, Digitalis., Linaria, Antirrhinum, and Globularia. This study synthesizes ethnobotanical data derived from theses, regional surveys, and peer-reviewed studies conducted across different phytogeographical regions of Türkiye. Methods: The key databases used were PubMed, Google Scholar, Web of Science, Scopus, and ScienceDirect. A list of precise keywords was used to improve the literature search process. The keywords included "Plantaginaceae," "traditional medicinal plants," "herbal medicine," "folk medicine," "ethnomedicine," "ethnobotany," "ethnopharmacology," and the geographical phrases "Turkey" and "Türkiye." Published sources from 1990 to 2026 were analyzed. Results: A total of 144 Use Reports (URs) across 22 taxa belonging to Plantaginaceae are documented including medicinal, food, veterinary, ornamental, and other traditional uses. Medicinal applications dominate the recorded uses, primarily targeting dermatological conditions, gastrointestinal disorders, respiratory ailments, inflammatory diseases, and metabolic disorders. Leaves and aerial parts are the most frequently utilized plant organs, and infusion, decoction, and poultice represent the dominant preparation methods. The prominence of Plantago species, particularly Plantago major, P. lanceolata, highlights their cultural and therapeutic importance in Turkish folk medicine. Conclusions: This review provides a comprehensive framework for understanding traditional knowledge patterns within the Plantaginaceae family in Türkiye and underscores their potential for future pharmacological, conservation, and sustainable-use studies. Keywords: Plantaginaceae; Traditional Medicinal Plants; Ethnobotany; Anatolia; Türkiye